2017
DOI: 10.1126/scisignal.aan3181
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity drives FMRP- and HSPG-dependent matrix metalloproteinase function required for rapid synaptogenesis

Abstract: Matrix metalloproteinase (MMP) functions modulate synapse formation and activity-dependent plasticity, with MMP dysfunction implicated in Fragile X syndrome (FXS), a disease caused by the loss of the RNA binding protein FMRP and characterized by neurological dysfunction and intellectual disability. Gene expression studies in Drosophila suggest that Mmps cooperate with the heparan sulfate proteoglycan (HSPG) glypican co-receptor Dally-like protein (Dlp) to restrict trans-synaptic Wnt signaling, and that synapto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 110 publications
3
38
0
Order By: Relevance
“…In the developing wing disk, the Wnt Wg is produced in a stripe of cells at the dorsal/ventral margin boundary, and acts as an intercellular morphogen through Fz2 receptor signaling (Bhanot et al, 1996;Zecca et al, 1996;Neumann and Cohen, 1997). The glypican HSPGs Dally and Dlp, bound to outer plasma membrane leaflets via GPI anchors, bind Wg to regulate both ligand distribution and intercellular signaling (Tsuda et al, 1999;Baeg et al, 2001;Dear et al, 2017). It has been proposed that Dally/Dlp HSPGs are involved in the movement of extracellular Wg to form a morphogen gradient (Han et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the developing wing disk, the Wnt Wg is produced in a stripe of cells at the dorsal/ventral margin boundary, and acts as an intercellular morphogen through Fz2 receptor signaling (Bhanot et al, 1996;Zecca et al, 1996;Neumann and Cohen, 1997). The glypican HSPGs Dally and Dlp, bound to outer plasma membrane leaflets via GPI anchors, bind Wg to regulate both ligand distribution and intercellular signaling (Tsuda et al, 1999;Baeg et al, 2001;Dear et al, 2017). It has been proposed that Dally/Dlp HSPGs are involved in the movement of extracellular Wg to form a morphogen gradient (Han et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cow could be considered an alternative extracellular Wg transport method (Chang and Sun, 2014), acting to shield Wg while facilitating transport through the extracellular synaptomatrix Dear et al, 2016). In addition, HSPGs have been shown to regulate ligands by stabilizing, degrading, or sequestering the ligand, or as bifunctional coreceptors, or as facilitators of transcytosis (Lin, 2004;Dear et al, 2017). Results presented here are consistent with the hypothesis that Cow is mediating Wg transport across the NMJ synapse (Chang and Sun, 2014), but also that Cow has an additional role in the negative regulation of Wg synaptic signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, this overly simplistic concept has been revised in recent years, as the effects of MMPs on ECM metabolism are not only of destructive character, but includes as well reparative functions, depending on the phase of MS. MMP-9 is involved in oligodendrocyte regrowth [203], while MMP-7 cleaves remyelination-impairing fibronectin to allow remyelination, and the authors speculate that a too low MMP-7 level contributes to the persistence of demyelination in chronic MS lesions and prevents oligodendrocyte maturation [204]. A further function of MMPs for synaptogenesis has been recognized [205,206]. These findings are relevant for the concept how MMP inhibition could be used as therapeutic approach in MS.…”
Section: Matrix Metalloproteinases In Multiple Sclerosismentioning
confidence: 93%
“…It remains unclear how octopamine signaling at type I synaptic regions regulates postsynaptic Dlp levels. Broadie and collaborators revealed that ECM metalloproteinases (Mmp1 and Mmp2) and the tissue inhibitor of metalloproteinases (Timp) play critical roles in synapse formation and activity-dependent plasticity in the Drosophila NMJ (Dear et al, 2016(Dear et al, , 2017Shilts and Broadie, 2017). Mmp2 from the presynaptic and postsynaptic compartments has been shown to negatively regulate synaptic Dlp levels at the NMJ, possibly by the proteolytic cleavage of Dlp core proteins (Wang and Page-McCaw, 2014).…”
Section: Discussionmentioning
confidence: 99%